Personality Traits As Predictors Of Burnout Syndrome Among Nurses In The University Of Port Harcourt Teaching Hospital Rivers State - Ekechukwu, R. O.; Isabella, Osuagwu (Advances in Social Sciences Research Journal, 2020)
The study investigated personality traits as predictors of burnout syndrome among nurses in the University of Port Harcourt Teaching Hospital Rivers State. The study used the correlational research design. The population of the study comprised of all 750 nurses in the University of Port Harcourt Teaching Hospital. A sample of 300 nurses from Paediatrics Ward, Male Ward, Female Ward and Intensive Care Unit (ICU), were randomly selected using the simple random sampling technique (balloting). Two instruments titled; Maslach Burnout Scale (MBS) by Maslach (1996) and Personality Inventory (NEO) by Costa and McCrae (1992) were used to collect data for the study. The Cronbach Alpha reliability was used to establish the internal consistency reliability coefficients of 0.87 and 0.81respectively. Responses to the research questions were analyzed with mean and standard deviation, while the hypotheses will be tested with multiple regression associated with independent sample t-test statistics. The findings of the study revealed that personality traits (neuroticism, extraversion, openness to experience) jointly predict burnout syndrome among nurses in University of Port Harcourt Teaching Hospital. Further analysis of the result showed that when personality traits of neuroticism, extraversion, openness to experience where looked at independently, only neuroticism and extraversion relate significantly predict burnout syndrome while openness to experience did not. Based on the findings of the study it was recommended among others that counsellors, psychologists and others in the helping profession should readily offer practical assistance to nurses experiencing burnout to enable them cope with the stressful experience they encounter in their daily work assignments.